Numerical simulation of blood flow and plaque progression in carotid–carotid bypass patient specific case. (2nd January 2015) - Filipovic, Nenad; Saveljic, Igor; Nikolic, Dalibor; Milosevic, Zarko; Kovacevic, Pavle; Velicki, Lazar
Abstract: This study describes computer simulation of blood flow and plaque progression pattern in a patient who underwent surgical treatment for infected carotid prosthetic tube graft using carotid–carotid cross-over bypass. The 3D blood flow is governed by the Navier–Stokes equations, together with the continuity equation. Mass transfer within the blood lumen and through the arterial wall is coupled with the blood flow and is modelled by the convection–diffusion equation. Low-density lipoprotein (LDL) transport in lumen of the vessel is described by Kedem–Katchalsky equations. The inflammatory process is solved using three additional reaction–diffusion partial differential equations. Calculation based on a computer simulation showed that flow distribution in the left carotid artery (CA) was around 40–50% of the total flow in the right common CA. Also, the left CA had higher pressure gradient after surgical intervention. Plaque progression simulation predicted development of the atherosclerotic plaque in the position of the right common CA and the left internal CA. A novel way of atherosclerotic plaque progression modelling using computer simulation shows a potential clinical benefit with significant impact on the treatment strategy optimization.